MEDICAL AND BIOLOGICAL EFFECTS ON HUMAN CONTACT WITH DANGEROUS PLANTS OF NORTH CAUCASUS - Mikhail Sergeyevich Dementyev; Sergei Aleksandrovich Emelyanov; Diana Mikhailovna Dementyeva (Современная наука и инновации, 2022)
Even in the context of technical changes a person is forced to coexist with wildlife. Some of them are dangerous to humans. For example, hundreds of people suffer from the effects of contact with plants. To date, however, the awareness about this issue is at an insufficient level.